FAKTOR- FAKTOR YANG MEMPENGARUHI PENGETAHUAN IBU PUS DALAM PEMAKAIAN KB DEPO MEDROXYPROGESTERONE ASETAT DI HENI KASIH MEDAN 2018 - Merlina Sinabariba (Elisabeth Health Jurnal, 2019)
The purpose of the Family Planning program is to create "Quality Families". Family Planning is an effort to increase the awareness and participation of urban society through Maturatingthe Age Marriage (PUP), Controlling birth, Fostering family resilience, Improving the welfare of small families. One of the contraceptives used by the community is the 3-month injection hormonal contraception, DMPA (DEPOT MEDROXYPROGESTERONE ACETATE). Depotmedroxyprogesterone acetate is a contraceptive which contains 25 mg medroxyprogesterone acetate and 5 mg Estradiol Cypionate called Cyclophem. This DMPA contraceptive injection is given every 3 months and must be injected in a deep intramuscular injections in the buttocks area. This medroxyprogesterone Acetate contraceptive injection has high effectiveness if it is carried out regularly according to a predetermined schedule. Methods : This research is descriptive which uses primary data through questionnaires distributed to all 3-month injectable family planning acceptors. Sampling in total population with a total of 33 respondents. Results: According to the results of the research based on the knowledge,out of 33 respondents, (39%) were knowledgeable enough and (27%) were less knowledge. Based on education, the majority had high school education with (66%), and a minority had a higher education/collegewith (3%). Based on the occupation, the majority of respondents (63%) were housewives, and self-employement were the minoritywith (36%). Based on parity, the majority (64%) had 2 children, and a minority (21%) had>3 children. Based on the economy, the majority (33%) out of 33 respondents earn <2,000,000. Based on sources of information, the majority (96%) of the environment and minority (6%) are from electronic media. Based on the age of the majority (94%) were 20-35 years old and a minority (6%) were > 35 years old. Conclusion: Therefore, based on the result of the resarch, the health workers are expected to notifyprospective family planning acceptors about 3 month injections of family planning.